Recovery Of Zinc From Steelmaking Dust - Tsuyoshi Miyashita (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1976)
Onahama Refinery of Ryoho Recycle Company employs the electrothermic process for producing marketable zinc oxide from steelmaking dusts. The process comprises washing, filtration, drying, sintering and furnacing. Fume from the sinter machine is treated hydrometallurgically to recover zinc, cadmium and lead.